2010
DOI: 10.1073/pnas.1003174107
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating neural subsystems for grammar by contrasting word order and inflection

Abstract: An important question in understanding language processing is whether there are distinct neural mechanisms for processing specific types of grammatical structure, such as syntax versus morphology, and, if so, what the basis of the specialization might be. However, this question is difficult to study: A given language typically conveys its grammatical information in one way (e.g., English marks "who did what to whom" using word order, and German uses inflectional morphology). American Sign Language permits eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 62 publications
(94 reference statements)
6
53
0
1
Order By: Relevance
“…An extensive portion of the right anterior/middle STS was also activated exclusively in signers. This region showed no specialization for linguistically structured material, although in previous studies we found sensitivity of this area to both morphological and narrative/prosodic structure in ASL (17,18). It thus seems that knowledge of a visual-manual sign language can lead to this region's becoming more sensitive to manual movements that have symbolic content, whether linguistic or not, and that activation in this region increases with the amount of information that needs to be integrated to derive meaning.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…An extensive portion of the right anterior/middle STS was also activated exclusively in signers. This region showed no specialization for linguistically structured material, although in previous studies we found sensitivity of this area to both morphological and narrative/prosodic structure in ASL (17,18). It thus seems that knowledge of a visual-manual sign language can lead to this region's becoming more sensitive to manual movements that have symbolic content, whether linguistic or not, and that activation in this region increases with the amount of information that needs to be integrated to derive meaning.…”
Section: Discussionmentioning
confidence: 81%
“…Our data revealed that, when sign language and gesture stimuli are closely matched for content, and once perceptual contributions are properly accounted for, a much more restricted set of brain regions are commonly engaged across stimulus types and groupsrestricted to middle and anterior regions of the right STS. We have consistently observed activation in this anterior/middle right STS area in our previous studies of sign language processing, in both hearing native signers and late learners (16) and in deaf native signers both for ASL sentences with complex morphology [including spatial morphology (18), and narrative and prosodic markers (17)]. The present findings extend this to nonlinguistic stimuli in nonsigners, suggesting that the right anterior STS is involved in the comprehension of symbolic manual communication regardless of linguistic structure or sign language experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across signed and spoken language, bloodflow increases to the left inferior frontal gyrus (LIFG) and left inferior parietal lobe (IPL) during phonemic discrimination (49,50) and morphosyntactic processing (51). Similarly, word production in both signed and spoken languages activates LIFG, left IPL, and left temporal areas (52).…”
Section: Neural Mechanisms Of Language Comprehension Across Sensorymentioning
confidence: 99%
“…Some indirect support for this last claim seems to come from research on the neural basis of processing. Newman et al (2010) found out in a series of neuroimagining experiments that processing constructions in a language like English that "typically conveys grammatical information…. using word order" (positional languages in our terminology) activated "left-lateralized areas involved in working memory and lexical access" while "inflectional morphology sentences activated areas involved in building and analyzing combinatorial structure".…”
Section: "The Human Parser Prefers Linear Orders That Maximize the Icmentioning
confidence: 99%